The Place of Man Between Self-Sovereignty and the Defeat of the System: A Comparative Study in Contemporary Philosophy (Comprehensive Journal of Science, 2026)
This research addresses the issue of the place of man in contemporary philosophies between self-sovereignty and the defeat of the system. The topic revolves around the ontological conflict between "self-sovereignty" as a free, conscious, and responsible entity, and the "defeat of the system," represented by the structures (linguistic, social, and technological) that precede and shape man. This issue has witnessed radical transformations as a result of scientific, technological, and social developments in the twentieth and twenty-first centuries. The research problem lies in observing the intellectual conflict between schools that have attempted to elevate the value of the "self" and its freedom, such as existentialism and personalism, and schools that have proclaimed the "death of man" or his decline in favor of larger systems (such as structuralism and postmodernism). This research employs a comparative analytical approach to deconstruct the vision of each school of thought and discuss how modern technology has influenced the concept of "humanity" in post-human philosophies. The research concludes that contemporary humans are no longer defined as static beings, but rather as anxious beings constantly rediscovering themselves amidst their struggle with machines on one hand, and with authoritarian systems on the other. It emphasizes the necessity of formulating a "new humanism" that safeguards human dignity in the digital age.
Keywords: Human – Philosophy – Self – System